Exploring the longevity of dry Craterostigma wilmsii (homoiochlorophyllous) and Xerophyta humilis (poikolichlorophyllous) under simulated field conditions - Bajic, Jelena (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (p.143-164).